The California Republic: Institutions, Statesmanship, and Policies - Janiskee, Brian P.; Masugi, Ken (Rowman & Littlefield Publishers, 2003)
Even before its budget crisis and recall election, California held a unique position in the United States. Often lauded as having the fifth largest economy in the world, California leads the nation in other measures as well, particularly cultural and political trends. But were it an independent state, it would have one of the world's most unusual democracies. In The California Republic Brian P. Janiskee and Ken Masugi bring together a diverse group of contributors to shed light on the Progressive nature of California government. In addition to thorough treatment of perennial issues like affirmative action, gun control, and education, the work goes outside the conventional understanding of political issues to examine such topics as the Hollywood western, the electronic media, and California's revolutionary founding. Accordingly, the contributors include not only political scientists and historians, but journalists and political activists as well. The result is a clear exploration of the evolution of Progressive government in California and its contemporary policy consequences.